This idea is brilliant : lost, overlooked, and underappreciated scientific concepts everyone should know - Brockman, John, 1941-; Milner, Yuri; Waytz, Adam; Rowan, David; Dawkins, Richard, 1941-; Fitch, W. Tecumseh; Lloyd, Seth, 1960-; Pinker, Steven, 1954-; Lisi, Antony Garrett; Losos, Jonathan B.; Church, George M. (George McDonald) (Harper Perennial, 2018)
Presents essays responding to a question about what scientific term or concept ought to be more widely known, written by such authors as Jared Diamond, Richard Thaler, Richard Dawkins, Lisa Randall, Steven Pinker, and Carlo Roveri.